Brain mechanisms of parenting in co-parenting spouses and parent-child dyads - Nur Atiqah Azhari (Nanyang Technological University, 2021)
Parenting is an integral part of human society that involves cooperation between co-parenting spouses (i.e., mother-father dyads) and bonding within parent-child dyads. Continuous exposure to a dyadic partners’ behavioural repertoire in daily life will lead to rhythmic patterns of interactions that are postulated to be supported by temporally similar underlying brain signals commonly referred to as inter-brain synchrony. Within the parenting context, mother-father dyads and parent-child dyads are two attachment pairs in which inter-brain synchrony is expected to be observed. Despite the ubiquity of bi-parental rearing in humans, studies on inter-brain synchrony in mother-father dyads are scarce. Studies on parent-child dyads have yet to investigate the effects of child, parental and stimuli characteristics on a child’s processing of narrative scenes during everyday joint activities like co-viewing children’s movies together. Moreover, the effects of maternal psychological factors on inter-brain synchrony have been minimally investigated. This thesis comprises four functional near-infrared spectroscopy (fNIRS) studies that have examined prefrontal cortex (PFC) brain mechanisms in dyadic parenting contexts. Study 1 investigated inter-brain synchrony in 24 mother-father dyads (N=48) who rear their infant together. In the everyday context, spouses are continually exposed to each other’s physical presence and to salient infant and adult vocalisations (e.g,. cry, laughter). To test the hypothesis that inter-brain synchrony would be enhanced when spouses are in each other’s physical presence, each couple was presented with salient vocalisations in two conditions: together (in the same room, at the same time) and separately (in different rooms, at different times). Findings showed that co-parenting spouses displayed significantly greater synchrony when together, and that this result was observed in true couples but not in control couples. Spouses also showed greater synchrony towards positive and neutral vocalisations, but not negative ones. These results imply that the physical presence of a spouse facilitates inter-brain synchrony in attentional brain regions, and that synchrony might be adaptive in favourable situations (i.e., exposure to laughter) but not under stressful conditions (i.e., exposure to cry). Study 2 transited to parent-child dyads and investigated inter-brain synchrony in mother-child pairs during a co-viewing paradigm. 31 mother-child dyads (N = 62) participated in this study, which investigated the effects of maternal parenting stress and maternal anxious attachment, on inter-brain synchrony during co-viewing of three 1-minute animation scenes. To test the hypothesis that greater parenting stress would be associated with reduced synchrony, mothers’ self-reported parenting stress was measured with a Parenting Stress Index (PSI) questionnaire. Findings supported this prediction as higher parenting stress was correlated with less synchrony in the medial left PFC cluster which is implicated in mentalisation processes and social cognition. This result implies that parenting stress undermines shared inter-subjective experiences between mother and child during co-viewing. Study 2 also investigated the effects of maternal attachment-related anxiety, measured using the Attachment Style Questionnaire (ASQ), on dyadic inter-brain synchrony and maternal brain responses during co-viewing of three 1-minute animation scenes. Since anxiously-attached mothers tend to be preoccupied with their child’s social cues, dyads with more anxiously-attached mothers were hypothesised to display reduced inter-brain synchrony during the co-viewing activity. Results showed that greater maternal attachment anxiety was associated with less inter-brain synchrony in the medial right cluster of the PFC which is critical for mentalisation. This finding suggests that there potentially exists a difference in the intersubjective experiences shared between a mother with anxious-related attachment and her child during everyday co-viewing activities. The implication borne out of the findings of Study 2 is that maternal psychological variables, namely parenting stress and attachment anxiety, could undermine the quality of shared experiences when dyads engage in passive bonding activities together. Finally, Study 3 measured children’s and parental brain processing when co-viewing narrative scenes. 62 children of preschool-age (37 boys, 25 girls) and their parents (29 fathers, 33 mothers) participated in a co-viewing activity (N = 124) which screened three 1-minute video excerpts of children’s movies of positive, neutral and negative emotional valences. Results showed that children displayed greater PFC activity when co-viewing with fathers than with mothers. Girls were also found to exhibit heightened PFC responses than boys towards the positive video stimulus. Analyses of mothers’ and fathers’ prefrontal responses revealed that parents from same-gendered dyads (i.e., mother-daughter, father-son) showed greater brain activation than parents from opposite-gendered dyads (i.e., mother-son, father-daughter) when watching a scene where the gender of the characters was salient. These findings suggest that social and stimuli factors in the environment influence parents’ and children’s processing of narrative scenes when co-viewing.